Tipologia de sistemas produtivos leiteiros no Paraná, a partir de aspectos de sustentabilidade - Prizon, Rodrigo César (2015)
The overall objective was to characterize and analyze Dairy Production Systems in the State of Paraná against environmental sustainability variables, social, economic. This is justified by the fact that there are new demands of society and government to production processes. Currently, one should not produce more focused only on the profit generated, it is essential to pay attention to the sustainability of production processes so that they have the possibility of repeated viably today and over time, respecting the environmental, economic and dimensions social. The agribusiness, especially the Agroindustrial Milk System has great potential impact on these three dimensions, due to its high economic and social importance, and to be inserted into the environment and use natural resources for the development of its activities. To analyze the sustainability in dairy production systems of Paraná, data were collected through interviews in 75 DPS. In the first article, there was the general characterization of the DPS. It was found that the three dimensions (environmental, economic and social) had overall average above the cutoff of notes, so most DPS are tailored to sustainability issues. However there is great variation between the DPS, demonstrating that there is well suited DPS and other less suitable. So it is important to identify these DPS and group them in order to generate a classification that differentiates them, facilitating specific actions for each group. In the second article, by multivariate analysis using the Common Factor analysis, principal component extraction and hierarchical agglomerative cluster analysis method, it was possible to identify and characterize these groups, in addition to showing the main components responsible for the variation of sustainability in DPS. 63.22% of the total variation in DPS were from four main components, namely a) the adequacy of production; b) technical and social suitability for sustainability; c) Suitability for environmental sustainability d) Suitability for economic sustainability. It was possible to form three clusters, the first being regarded as a reference, as it showed great medium for all components; the second was the cluster with the largest amount of DPS and considered adequate in the three dimensions, but with some means close to the cut-off point; and the third cluster was considered DPS with critical features for sustainability, as presented little adaptation, with some medium below the cutoff score.